Identification of protein N-termini in Cyanophora paradoxa cyanelles: transit peptide composition and sequence determinants for precursor maturation - Köhler, Daniel; Dobritzsch, Dirk; Hoehenwarter, Wolfgang; Helm, Stefan; Steiner, Jürgen; Baginsky, Sacha (Frontiers in Plant Science, 2015)
Glaucophyta, rhodophyta and chloroplastida represent the three main evolutionary lineages that diverged from a common ancestor after primary endosymbiosis. Comparative analyses between members of these three lineages are a rich source of information on ancestral plastid features. We analyzed the composition and the cleavage site of cyanelle transit peptides from the glaucophyte Cyanophora paradoxa by terminal amine labelling of substrates (TAILS), and compared their characteristics to those of representatives of the chloroplastida. Our data show that transit peptide architecture is similar between members of these two lineages. This entails a comparable modular structure, an overrepresentation of serine or alanine and similarities in the amino acid composition around the processing peptidase cleavage site. The most distinctive difference is the overrepresentation of phenylalanine in the N-terminal 1-10 amino acids of cyanelle transit peptides. A quantitative proteome analysis with periplasm-free cyanelles identified 42 out of 262 proteins without the N-terminal phenylalanine, suggesting that the requirement for phenylalanine in the N-terminal region is not absolute. Proteins in this set are on average of low abundance, suggesting that either alternative import pathways are operating specifically for low abundance proteins or that the gene model annotation is incorrect for proteins with fewer EST sequences. We discuss these two possibilities and provide examples for both interpretations.